Loyalitas Kerja Guru Senior dalam Perspektif Kepemimpinan Spiritual: Studi Kasus di SMA Swasta Islam Ulun Nuha Medan - Dea Annisa Seswoyo; Umi Kalsum; Zainidah Siagian (Lembaga Yasin AlSys, 2026)
Although studies on the work loyalty of senior teachers have received attention in several studies, research that specifically examines it from the perspective of spiritual leadership remains limited. This study aims to analyze the work loyalty of senior teachers from the perspective of spiritual leadership. This study employed a qualitative approach with a case study design. The data sources included senior teachers at SMA Islam Swasta Ulun Nuhai in Medan who had at least five years of work experience, as well as the principal and vice principal. Data were collected through in-depth interviews, observation, and documentation, then analyzed using a descriptive qualitative approach through the stages of data collection, data reduction, data presentation, interpretation, and conclusion drawing. The results showed that the work loyalty of senior teachers was influenced by the strengthening of moral values, a work atmosphere that appreciates the role of teachers, and the active involvement of teachers in the school environment. These findings affirm that work loyalty in education is not sufficiently built through a merely administrative approach, but needs to be supported by spiritual leadership that is able to foster a sense of being valued, attachment, and dedication naturally without coercion. This study contributes to the development of work loyalty theory by expanding understanding of the role of spiritual leadership in building the commitment of senior teachers. The practical implications of this study emphasize the importance of schools providing moral guidance and creating a supportive work environment to strengthen teacher loyalty. In addition, this study opens opportunities for further research on the factors that influence low work loyalty among Generation Z.